Early life maltreatment and depression: mediating effect of maternal hair cortisol concentration on child abuse potential - Kluczniok, Dorothea; Bertsch, Katja; Neukel, Corinne; Fuchs, Anna; Herpertz, Sabine (Psychoneuroendocrinology, 2020)
Introduction - Maternal early life maltreatment (ELM) and history of depression can bear a risk for adverse development in the child. One neurobiological pathway for the transmission of both maternal ELM and remitted depression (MDD) might be altered maternal cortisol levels. In the present study, we examine (1) main and interacting effects of maternal ELM and remitted MDD on hair cortisol concentration (HCC) in mothers, whether (2) maternal HCC explains the association between maternal ELM or remitted MDD and maternal child abuse potential, and (3) whether maternal child abuse potential as well as maternal HCC are associated with maternal report of child well-being. - Methods - The current study involved 127 mother-child dyads. Maternal history of ELM and psychopathology were assessed via the Mini International Neuropsychiatric Interview (M.I.N.I.) and Childhood Experience and Care (CECA) interview. The Child Abuse Potential Inventory (CAPI) was used to assess maternal child abuse and neglect potential. We applied the Kidscreen-27 parent report to study child well-being. To assess HCC, hair strands were taken from the mothers. To test the research questions, a two-factorial analysis of covariance, mediation analysis using ordinary least squares regressions with bootstrapping, and Pearson correlations were calculated. - Results - Mothers with ELM had significantly increased HCC. There was no effect of remitted MDD on HCC, nor an interaction effect of both factors. HCC was a significant mediator of the association between maternal ELM and maternal child abuse potential. Maternal child abuse potential as well as HCC were significantly associated with reduced child well-being. - Discussion - Our data suggest that adverse experiences in childhood are associated with altered HPA-axis functioning reflected in increased levels of HCC. HPA-axis activity is not altered in mothers with remitted MDD. From a clinical point of view, one might speculate that the partially mediating effect of maternal HCC could indicate a starting point in the prevention of the intergenerational cycle of abuse.